What makes a doctor a scholar: a systematic review and content analysis of outcome frameworks. Issue 1 (December 2016) - Hautz, Stefanie; Hautz, Wolf; Feufel, Markus; Spies, Claudia
Abstract Background Many national outcome frameworks (OF) call for a sound scholarship education and scholarly behaviour of physicians. Educators however are known to interpret the scholar role in markedly different ways and at least one major initiative to unify several national outcome frameworks failed to agree on a common definition of the scholar role. Both circumstances currently limit the development of educational and assessment strategies specific for the scholar role. Given increasing physician mobility together with the global perspective inherent in a doctor's role as a scholar, we were interested in what different OFs define as the scholar role and attempted to identify communalities and differences between them. Methods We conducted a systematic review for OF in medical education in PubMed and google. After in- and exclusion processes, we extracted all content listed under the scholar role (if present) and categorized it based on Boyer's established model of scholarship. Next, we extracted all content related to scholarship from OFs not explicitly defining a scholar role and used it to validate the categories resulting from step one. Results From 1816 search results, we identified 13 eligible OFs, seven of which explicitly specified a scholar role. The outcomes only partly map onto Boyer's definition of scholarship: Discovery, Integration, Application, and Teaching. We adapted and validated a model extending this definition to contain Common Basics (partly overlapping with Integration and Teaching), Clinical Application (specifying Application), Research (Discovery and partly Integration), Teaching and Education (partly overlapping with Teaching) and Lifelong Learning (no equivalent in Boyer's model). Whereas almost all OFs cover Common Basics, Clinical Application, and Lifelong Learning, fewer and less specific outcomes relate to Research or Teaching. Conclusions The need to adapt existing models of scholarship may result from the changing demands directed at medical scholars. The considerable differences identified between OFs may explain why educators have difficulties defining the scholar role and why the role is rarely assessed. We may have missed OFs due to our in- and exclusion criteria but the results provide a solid basis on which to build a common understanding of what makes a doctor a scholar.